2011
DOI: 10.1002/lary.21812
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine—An efficient and cost‐effective approach in parathyroid surgery

Abstract: TeleHealth is a cost-effective and efficient way to follow-up with patients who have undergone parathyroidectomy, with significant convenience and financial benefits for the patient and healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 21 publications
2
80
0
1
Order By: Relevance
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported no complications in either group. 47,50,52 Though too heterogeneous in design to perform a formal meta-analysis, taken as a whole, the overall rate of complications in patients receiving care via telemedicine was 2.8% (7 of 254) compared with a rate of 0.4% (1 of 242) in patients receiving usual care. Beyond complication rates, Cleeland and colleagues 43 reported more rapid improvement in postoperative symptoms in patients after thoracotomy for lung cancer or lung metastases through the use of telemedicine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The previous studies noted in the literature for surgical subspecialties were generally same-day, non-reconstructive surgeries with little visual assessment required. 13 Our study group contained patients undergoing hypospadias repair, which is comparatively more complex and has a greater need for visualization of the surgical site during follow-up. This suggests that telemedicine can be used for follow-up in patients having both complex and less complex post-operative evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…18 Postoperative telehealth visits for patients who had undergone parathyroidectomy were found to be cost-effective and efficient. 19 In Europe, costs for implantable cardiac defibrillator remote follow-up visits were found to be essentially the same as those for in-office follow-up visits. 20 A few studies provide information about the knowledge, attitudes, and adoption of telehealth services among health care providers.…”
mentioning
confidence: 93%